Hot Deformation Behavior of V-Microalloyed Steel - REN, An-chao; JI, Yu; ZHOU, Gui-feng; YUAN, Ze-xi; HAN, Bin; LI, Yi (Journal of iron and steel research, international, 2010)
Through the expansion curve of continuous cooling transformation at different cooling rates measured by THERMECMASTOR-Z thermal simulator for U75V rail steel,the continuous cooling transformation curve was obtained.The influence on steel microstructure and hardness at different cooling rates was studied.The softening behavior of isothermal deforming in austenite area of 850-1000 ℃ in the interval of passes was also studied by double-pass compression test.The results show that the product of austenite transformation is pearlite when the cooling rate is lower than 10 ℃.When the cooling rate was in the range of 10-50 ℃·s-1,only martensite was received.The hardness of the test steel increases with increasing the cooling rate.Under the condition of deformation of 30% and deformation rate of 3 s-1,the relaxation time for complete recrystallization was shorter than 100 s when deformation temperature was higher than 1000 ℃.When deformation temperature was lower than 880 ℃,complete recrystallization of steel was difficult to achieve even if the relaxation time is extended.